(untitled) (Medical Forum Monthly, 2021)
Objective: To evaluate outcome pattern, clinical characteristics of stroke and to compare outcome pattern in diabetic and non-diabetic patients. Study Design: Cross sectional study Place and Duration of Study: This study was conducted at the department of medicine at DG Khan Medical College & Teaching Hospital, DG Khan and QAMC Bahawalpur from July, 2019 to June, 2020. Materials and Methods: Sixty patients of stroke were enrolled in study and allocated in two groups on basis of their diabetic status (Yes/No). Patients were treated and diagnosed as per ward protocol. All patients of age >20 years presenting with findings of stroke hemi anesthesia, hemiparesis, vertigo, language dysfunction and altered sensorium were included. Main outcomes were infarct size, hemorrhage and prognosis. SPSS version 23 was used for data analysis. Test of significance were applied and p value less than or equal to 0.05 was taken as significant. Results: The diabetes was noted in 60.0% patients. Infarct is the predominant pattern occurring in 58.3% patients and hemorrhage was observed in 56.6% patients. Good prognosis was noted in 45.0% patients and bad prognosis was observed in 55.0% patients. The difference was statistically significant between prognosis and diabetes status, (p=0.000). Conclusion: Undoubtedly diabetes is risk factor for stroke that should be watched and considered. Pattern of outcomes and prognosis is much different in diabetic stroke patients as compare to non-diabetics